Preconditioning Block Lanczos Algorithm for Solving Symmetric Eigenvalue Problems (Journal of Computational Mathematics, 2000)
A preconditioned iterative method for computing a few eigenpairs of large sparse symmetric matrices is presented in this paper. The proposed method which combines the preconditioning techniques with the efficiency of block Lanczos algorithm is suitable for determination of the extreme eigenvalues as well as their multiplicities. The global convergence and the asymptotically quadratic convergence of the new method are also demonstrated.
Keywords: eigenvalue; eigenvector; sparse matrices; Lanczos method; preconditioning.